Revascularization of superficial femoral artery due to chronic total occlusion: Collateral approach - Özkan Candan; Sabahattin Gündüz; Müslüm Şahin (KARE Publishing, 2018)
Endovascular interventions are now used more frequently in the treatment of femoropopliteal occlusions, and antegrade passage through the occlusion is preferred as the first option. However, when antegrade passage fails for any of several reasons, retrograde, or less frequently, collateral passage may be used. Although collateral passage may present serious complications, it can be successfully applied in selected cases in experienced centers. In the present case, a superficial femoral artery occlusion was successfully opened with a collateral approach.